1992
DOI: 10.1002/nbm.1940050308
|View full text |Cite
|
Sign up to set email alerts
|

31P NMR spectroscopy of perinatal hypoxic‐ischemic brain damage: A model to evaluate neuroprotective drugs in immature rats

Abstract: Cerebral energy metabolism can be measured non-invasively in unanesthetized neonatal rats with 31P NMR spectroscopy. Using this technique, serial changes in high energy phosphates were determined from the right cerebral hemispheres of 7 day postnatal rat pups during a hypoxic-ischemic insult known to produce focal brain injury. During 3 h of hypoxia-ischemia the concentration of ATP dropped to 33 +/- 8% of prehypoxic (baseline) levels, phosphocreatine (PCr)/Pi decreased from 1.5 +/- 0.51 to 0.16 +/- 0.06, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 39 publications
(2 reference statements)
3
5
0
Order By: Relevance
“…6). There is a strong correlation between the P i /PCr ratio and the neuropathologic score, which agrees with previous reports (7,9,10). Animals with larger integrated P i /PCr values tend to have severe damage at 24 h post HI, whereas animals pretreated with DEX show no neuronal loss with P i /PCr ratios under 3.…”
Section: Resultssupporting
confidence: 91%
“…6). There is a strong correlation between the P i /PCr ratio and the neuropathologic score, which agrees with previous reports (7,9,10). Animals with larger integrated P i /PCr values tend to have severe damage at 24 h post HI, whereas animals pretreated with DEX show no neuronal loss with P i /PCr ratios under 3.…”
Section: Resultssupporting
confidence: 91%
“…5,30,[39][40][41][42][43] Although the duration of the insult is variable (2 min to several hours), all studies found a sharper drop in PCr than in ATP, in agreement with our observations not only for hypoxia but also for ischemia and hypoglycemia. This behaviour reflects the buffering of the ATP level at the expense of PCr.…”
Section: Discussionsupporting
confidence: 91%
“…2, Table 4) resembled those reported in previous studies, including those of newborn animals (8,9,(23)(24)(25). The profound decrease in pH, was attributable in part to production of lactic acid.…”
Section: T I M E F R O M S T a R T Of R E S U S C I T A T I O N ( H Osupporting
confidence: 86%
“…Most studies of cerebroprotection have involved very small animals, such as the newborn rat, which are particularly useful for screening for suitable pharmacologic agents (23,28). Before cerebroprotective strategies are applied to human infants who have suffered a severe acute hypoxic-ischemic insult to the brain, it will bc important to prove their worth in a suitable animal model that is large enough for a wide range of systemic as well as cerebral observations to be made.…”
Section: T I M E F R O M S T a R T Of R E S U S C I T A T I O N ( H Omentioning
confidence: 99%